Study of secondhand smoke levels pre and post implementation of the comprehensive smoking ban in Mumbai - Deshpande Aditi; Kudtarkar Priyanka; Dhaware Dhanashri; Chowgule Rohini (Wolters Kluwer Medknow Publications, 2010)
Objectives: This research was undertaken with the aim of assessing the indoor air quality in popular hospitality venues, as also to evaluate the effectiveness of the nationwide comprehensive public smoking ban. The analysis was split into two halves - baseline study taken up prior to implementation of the said ban on 2 nd October 2008, and the follow-up study after it came into effect. Materials and Methods: Twenty-five venues including five restaurants, fourteen resto-bars, two hookah (smoking water-pipe) cafes and four pubs were selected using a mix of random, convenience and purposeful sampling. Particulate matter (PM 2.5 ) measurements at these venues were made using TSI SidePak AM510 Personal Aerosol Monitor. Results: The average PM 2.5 level in venues where smoking was permitted prior to implementation of ban was found to be 669.95 ΅g/m 3 in the baseline study. Post ban, the average PM 2.5 level in same test venues reduced to 240.8 ΅g/m 3 . The hookah cafes were an exception as the average PM 2.5 levels exceeded the permissible limits before as well as post ban. Conclusion: The baseline study showed that the hospitality venues had hazardous levels of PM 2.5 particles arising from second-hand smoke prior to smoking ban. These decreased by a maximum of 64% after the law took effect. A substantial improvement in air quality at these venues post implementation of the smoking ban indicated the effectiveness of the law.